POLA ASUH ORANG TUA DALAM PENGGUNAAN ALAT KOMUNIKASI HANDPHONE DAN MEDIA INTERNET BERDASARKAN KARAKTERISTIK WILAYAH DIKECAMATAN PAUH DAN PADANG TIMUR - Febiola, Feby - (Pendidikan Geografi, 2014)
With the technological advances in the field of mobile communication devices andmedia, the internet, indispensable role of parents in educating their children. The role ofparenting parents is very important. Characteristic areas of the city with its suburbs isdifferent. Likewise with parenting parents area of the city with its suburbs.This study aims to determine the comparative parenting parents in the use of mobilecommunication devices and internet media based on the characteristic region in the district ofPadang Pauh and District East. The research is a comparative descriptive. The population inthis study were all families (KK) in the district of Padang Pauh and District East. Sampleswere taken in two ways, the samples were taken by taking a representative region of theterritory contained in the population and proportional random sampling technique with aproportion of 2% of the sample so that the sample of the study area amounted to 121households.Results of the study found that (1) There are different types of parenting parents in theuse of mobile communication devices and internet media in the region based on thecharacteristics of the sub-district and sub-district of Padang Pauh East. Where theauthoritative parenting parents in the village Cupak Tangah higher than that in the village ofKubu In Kerakah Parak. While permissive parenting parents in the village of Kubu In ParakKerakah higher than in Sub Cupak Tangah, (2) There is no difference in parenting parents inthe use of mobile communication devices and internet media in the region based on thecharacteristics of the village and the village of Kubu Cupak Tangah In Parak Kerakah termsof the level of parental education (3) There are differences in parenting parents in the use ofmobile communication devices and internet media in the region based on the characteristicsof the village and the village of Kubu Cupak Tangah Parak Kerakah in terms of livelihood ofthe elderly, (4) There is a difference parenting parents in the use of mobile communicationdevices and internet media in the region based on the characteristics of the village and thevillage of Kubu Cupak Tangah Parak Kerakah in terms of parental income.